1995
DOI: 10.1002/em.2850250110
|View full text |Cite
|
Sign up to set email alerts
|

Relative genotoxic activities of pesticides evaluated by a modified SOS microplate assay

Abstract: The genotoxic activities of 47 pesticides were determined using a modified SOS microplate assay in which the induction of beta-galactosidase in E. coli PQ37 was used as a quantitative measure of genotoxic activity. The results were compared with those obtained with anethole, curcumin, and capsaicin, a few examples of naturally occurring compounds present in foods. The assays were conducted with pesticides dissolved either in a suitable solvent, such as 10% DMSO in physiological saline or dispersed in sodium ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…To assess the contributions of HPV16 E6 and E7 in HNSCC, we employed a strategy previously used to induce oral and esophageal cancers in nontransgenic mice (31). This strategy makes use of 4NQO, a carcinogen that, although not a natural tobacco derivative, causes a spectrum of DNA damage similar to that caused by tobacco-derived carcinogens (26)(27)(28)(29)(30). Groups of HPV16-transgenic (K14E6͞K14E7) mice and nontransgenic mice were treated for 16 weeks with 4NQO dissolved in their drinking water at a dose 1͞10th of that used in the previous study (31).…”
Section: K14e6͞k14e7-transgenic Mice Are More Susceptible To 4nqo-indmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the contributions of HPV16 E6 and E7 in HNSCC, we employed a strategy previously used to induce oral and esophageal cancers in nontransgenic mice (31). This strategy makes use of 4NQO, a carcinogen that, although not a natural tobacco derivative, causes a spectrum of DNA damage similar to that caused by tobacco-derived carcinogens (26)(27)(28)(29)(30). Groups of HPV16-transgenic (K14E6͞K14E7) mice and nontransgenic mice were treated for 16 weeks with 4NQO dissolved in their drinking water at a dose 1͞10th of that used in the previous study (31).…”
Section: K14e6͞k14e7-transgenic Mice Are More Susceptible To 4nqo-indmentioning
confidence: 99%
“…Because tobacco use is implicated in HNSCC, we monitored cancers in K14E6͞K14E7 doubly transgenic mice treated with the chemical carcinogen, 4-nitroquinoline 1-oxide (4NQO). 4NQO causes a spectrum of DNA damage similar to that caused by tobacco-associated carcinogens (26)(27)(28)(29)(30), and it induces cancers of the oral cavity in rodents when it is supplied in their drinking water (31). 4NQO-treated, HPV16-transgenic mice developed HNSCC at a much higher frequency than nontransgenic mice.…”
mentioning
confidence: 99%
“…Spicy foods may play some role in human carcinogenesis, and to date one single epidemiological study has demonstrated that there was a correlation between hot chilli pepper consumption and incidence of gastric cancer (2); however, other studies have failed to provide evidence for its genotoxic potential (3,4). Capsaicin extracts have been extensively investigated for their effects on genotoxicity and mutagenicity in vitro as well as in vivo, but the study results are conflicting (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…4NQO is a water-soluble quinoline derivative that can cause DNA adduct formation, resulting in adenosine substitution for guanosine [26][27][28] . 4NQO may also undergo redox cycling to produce reactive oxygen species that result in mutations and DNA strand breaks 29,30) .…”
Section: Discussionmentioning
confidence: 99%